Performance Improvement of Coal Dust Briquettes: Application of Taguchi Design and Pareto Analysis for Optimizing Key Processing Variables - Dharta, Yuli; Wahyudie, ilham Ary; Sukanto, Sukanto; Husman, Husman; Yuliyanto, Yuliyanto; Oktriadi, Yudi (Universitas Sultan Ageng Tirtayasa, 2025)
The main challenge in the briquette-making process is selecting the appropriate and proportionate reinforcement or adhesive. The chosen adhesive must not only provide strong adhesion but also be compatible with other components. Briquettes are alternative fuels in solid form, made from carbon-containing materials with a high calorific value, allowing them to burn for an extended period. Coal is one of the alternative materials that can be used for briquettes. The choice of adhesive type and composition directly influences the compressive strength, thermal stability, and durability of briquettes in various environmental conditions. This study aims to investigate how process parameters affect the compressive strength of briquettes produced from coal powder reinforced with molasses, to improve the efficiency of the briquette production process. The methodology used in this study is the Taguchi method. The process parameters include four factors, each with three levels, tested with three replications: the percentage of reinforcement or adhesive at levels of 10%, 12.5%, and 15%; pressure at levels of 8 MPa, 10 MPa, and 12 MPa; temperature at levels of 70 °C, 90 °C, and 110 °C; and heating time at levels of 60 minutes, 90 minutes, and 120 minutes. To enhance the comprehensiveness of the study, several factors, including the moisture content of the briquettes, have also been examined. The results indicate that the temperature during the drying process is the most significant factor influencing the production of these briquettes.